2021
DOI: 10.3389/fpsyt.2020.624091
|View full text |Cite
|
Sign up to set email alerts
|

Case Report: Successful Implementation of Integrative Cognitive Remediation for Early Psychosis

Abstract: Many individuals demonstrate functionally relevant impairment in neurocognition as well as social cognition early on in the course of their psychotic disorder. There is robust evidence supporting cognitive remediation as an effective treatment of cognitive dysfunction in schizophrenia. Increasingly it is accepted that earlier treatment is associated with better outcome and that it is important to systematically assess and treat cognitive dysfunction before the cognitive and functional disabilities are fully re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 21 publications
1
1
0
Order By: Relevance
“…One German study with mental healthcare professionals ( N = 657) investigating the implementation of current evidence- and consensus-based guidelines for schizophrenia found that cognitive remediation was perceived as effective by less than one-half and referred by less than one-fifth of respondents, deviating from a strong guideline recommendation ( Gaigl et al, 2021 ). This is consistent with the results of an implementation case study of cognitive remediation in Icelandic early psychosis services, where clinical directors reported staff attitudes as one of the most important factors influencing implementation, along with patient needs ( Vidarstottir et al, 2021 ). Overall, available findings suggest that implementation strategies for behavioural cognitive remediation treatments may benefit from focusing on supporting engagement from both clinicians and patients.…”
Section: What Is Known About the Implementation Of Treatments Targeti...supporting
confidence: 87%
See 1 more Smart Citation
“…One German study with mental healthcare professionals ( N = 657) investigating the implementation of current evidence- and consensus-based guidelines for schizophrenia found that cognitive remediation was perceived as effective by less than one-half and referred by less than one-fifth of respondents, deviating from a strong guideline recommendation ( Gaigl et al, 2021 ). This is consistent with the results of an implementation case study of cognitive remediation in Icelandic early psychosis services, where clinical directors reported staff attitudes as one of the most important factors influencing implementation, along with patient needs ( Vidarstottir et al, 2021 ). Overall, available findings suggest that implementation strategies for behavioural cognitive remediation treatments may benefit from focusing on supporting engagement from both clinicians and patients.…”
Section: What Is Known About the Implementation Of Treatments Targeti...supporting
confidence: 87%
“…Cognitive remediation was successfully implemented at 13 of 16 adult Psychiatric Centres in rural and urban settings across New York state, with quality assurance data indicating that the treatment was acceptable, sustainable and effective. In Iceland, research on cognitive remediation delivered in early psychosis services included an effectiveness study and an implementation case study, which found cognitive remediation was successfully integrated into routine care using a range of strategies including training and education, supported by academic partnerships and a local implementation team ( Vidarstottir et al, 2021 ). However, without testing different implementation strategies and comparing implementation outcomes, it is not currently clear which strategy is most appropriate in which context.…”
Section: What Is Known About the Implementation Of Treatments Targeti...mentioning
confidence: 99%